2014
DOI: 10.1080/13527266.2014.973436
|View full text |Cite
|
Sign up to set email alerts
|

Country reputation as a moderator of tourism advertising effectiveness

Abstract: This study examines the role that country reputation plays in moderating the effects of tourism advertising for that country as well as attitude toward its government and citizens. A pre/post online study conducted in Australia used the current Brand USA's 'Land of Dreams' television commercial as the experimental stimulus. The country reputation scale was factor analyzed to reveal three underlying dimensionsLeadership, Investment, and Culture. Results indicated that Leadership moderated the effectiveness of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
0
17
0
1
Order By: Relevance
“…For example, applying the CRI to measure South Korea’s reputation, Yang et al (2008) identified emotional appeal, physical appeal, financial appeal, leadership appeal, cultural appeal, political appeal, and global appeal as the constructs that should be used to measure a country’s image. Fullerton and Kendrick (2017) applied the index to examine the role a country’s reputation plays in moderating the effects of tourism advertising for that country as well as attitude toward its government and citizens. They found that leadership moderated the effectiveness of the tourism ad for Australians’ interest in traveling to the USA as well as for attitude toward the US government.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, applying the CRI to measure South Korea’s reputation, Yang et al (2008) identified emotional appeal, physical appeal, financial appeal, leadership appeal, cultural appeal, political appeal, and global appeal as the constructs that should be used to measure a country’s image. Fullerton and Kendrick (2017) applied the index to examine the role a country’s reputation plays in moderating the effects of tourism advertising for that country as well as attitude toward its government and citizens. They found that leadership moderated the effectiveness of the tourism ad for Australians’ interest in traveling to the USA as well as for attitude toward the US government.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…1 Researchers have developed a number of conceptualizations of national image and instruments to measure it, such as Anholt-GFK Roper Nation Brands Index (NBI) (Anholt, 2006) and the Fombrun - RI Country Reputation Index (CRI) (Passow et al, 2005). Such conceptualizations and instruments have been widely used in public diplomacy studies (Fullerton and Kendrick, 2017; Kang and Yang, 2010; Kiambi and Shafer, 2018; Yang et al, 2008). They may as well be applied to the research in international tourism.…”
Section: Introductionmentioning
confidence: 99%
“…CRI is a flexible scale and it does not need much modification to measure the general characteristics of a particular country. The multidimensionality of the scale to measure country reputation (Holtzhausen and Fullerton, 2013;Yang et al, 2008;Fullerton and Kendrick, 2014), and evidence of it being validly applied in appraising country reputation from an internal stakeholders' perspective in previous studies (e.g., Passow et al, 2005)gives good justification to employ CRI in the present study. Moreover, CRI provides valuable insights into those aspects of the respondents' perceptions that drive the overall image of a country and thus, provide governments with measurement data that can be easily translated to pragmatic action plans (Passow et al, 2005).…”
Section: Importance To Identitymentioning
confidence: 98%
“…A study examined the role of the country's reputation in moderating the influence of tourism advertising for the country as well as attitudes towards the government and its citizens. A country's reputation scale was expressed in three dimensions: leadership, investment, and culture; where leadership moderated the effectiveness of tourism advertisements for visiting a country and attitudes towards the government of that country (Fullerton & Kendrick, 2017). Power played an essential role in building an influential reputation in a cooperative network and is therefore vital in planning and decision making.…”
Section: Government Marketingmentioning
confidence: 99%
“…of a brand that was given within a specific time to the target customer or project to influence the behaviour of the target audience (Bassano et al, 2019). There were various perspectives and emphasis on Integrated Marketing Communication, for example: combining offline and online with social media in marketing communication; integrated marketing communications advertising, promotion, and other forms (Fullerton & Kendrick, 2017); and, viewing advertising and promotion from the perspective of integrated marketing communication.…”
Section: Integrated Marketing Communicationmentioning
confidence: 99%